Meat Yield from Broiler, Indigenous Naked Neck and Full Feathered Chicken of Bangladesh (The Agriculturists, 2012)
Six males and 6 females in each genetic group (G) of broiler (Br), indigenous naked neck (Nana) and full feathered chicken (nana) at set three weight groups (WG); 0.75 kg, 1.00 kg and 1.25 kg were collected from different local markets and slaughtered. Meat yield traits of slaughtered chickens were recorded to identify a suitable G at a specific weight by comparing the meat yield of 3 Gs. Broiler had the highest breast, breast: dark meat and heart weight followed by Nana and nana while Nana had the highest gizzard weight followed by nana and Br. Dark, thigh, and giblet weight tended to increase in Nana followed by nana and Br. Male performed better than female for yielding meat except breast: dark meat and abdominal fat which was higher in female than that in male. The highest breast: dark meat of broiler, Nana and nana was observed in 1.00 kg, 0.75 kg and 1.25 kg WG, respectively. Indigenous chickens showed decreased head and feather weight but increased skin weight with increasing live weight. Notwithstanding, the highest skin weight was observed in Br followed by nana and Nana. The remarkable interaction of G x sex (S), G x WG, and G x S x WG was observed for breast: dark. The above findings reveal that Nana is comparable to Br, and better than nana for yielding meat. Of the feathering types, broiler is superior to nana for yield of meat. However, more studies are needed to confirm these findings. DOI: http://dx.doi.org/10.3329/agric.v10i2.13142 The Agriculturists 2012; 10(2) 55-67